2016
DOI: 10.1016/j.bbrc.2016.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and phenotypic analysis of an Mstn knockout rat

Abstract: Myostatin (Mstn) is an inhibitor of myogenesis, regulating the number and size of skeletal myocytes. In addition to its myogenic regulatory function, Mstn plays important roles in the development of adipose tissues and in metabolism. In the present study, an Mstn knockout rat model was generated using the zinc finger nuclease (ZFN) technique in order to further investigate the function and mechanism of Mstn in metabolism. The knockout possesses a frame shift mutation resulting in an early termination codon and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Further studies utilizing MSTN transgenic animal models indicated that it mainly promotes fat mass accumulation. For example, MSTN gene knockout in animals mainly leads to reduced fat mass and resistance to diet-induced obesity [39, 41]. MSTN inhibition in animals leads to reductions in fat tissues [46, 48, 49].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies utilizing MSTN transgenic animal models indicated that it mainly promotes fat mass accumulation. For example, MSTN gene knockout in animals mainly leads to reduced fat mass and resistance to diet-induced obesity [39, 41]. MSTN inhibition in animals leads to reductions in fat tissues [46, 48, 49].…”
Section: Resultsmentioning
confidence: 99%
“…In aging mice, the body fat percentage was also lower in MSTN KO compared with WT [40]. Decreased fat accumulation and increased muscle mass were also observed in MSTN KO rats [41] and pigs compared with wild type animals [42]. Previous research indicated that adipocytes and myocytes are both derived from the same mesodermal precursor [2].…”
Section: Mstn Deletion Mainly Leads To Increased Muscle Mass Reducedmentioning
confidence: 99%
“…SLC9A3R1 affects osteogenesis by mineralizing osteoblasts, and disrupting this gene resulted in reduced body weights in mice (90). MSTN is an important gene in the regulation of muscle cell growth and differentiation (91), and mutations in MSTN affect the muscle mass of goat (92), sheep (93), and cattle (94,95) as well as other mammals (96,97). These results indicate that SLC9A3R1 and MSTN might be targets of natural selection favoring increased body sizes ( fig.…”
Section: Evolution Of Body Size In Ruminantsmentioning
confidence: 91%
“…Mice carrying a targeted deletion of the Mstn gene exhibit dramatic muscle growth, with individual muscles weighing about twice as much as those of wild type mice ( 2 ). The function of MSTN has been strongly conserved through evolution, as targeted or naturally occurring mutations in cattle ( 3 5 ), sheep ( 6 ), dogs ( 7 ), rabbits ( 8 ), rats ( 9 ), swine ( 10 ), and goats ( 11 ) have all been shown to lead to increased muscling. Moreover, a heavily muscled boy was found to carry a mutation in a splice site in the MSTN gene, showing that MSTN plays a similar role in humans as well ( 12 ).…”
mentioning
confidence: 99%